A legal study on the occupational safety of Foreign Workers in the Construction Industry / Dayang Asmah Awang Hambali … [et al.] - Awang Hambali, Dayang Asmah; Fadzil, Noor Fazwani; Asngari, Noor Azee Ashikeen; Othman Ali, Hanis Syuhada (2010)
This research touches on the issue of protection that is given to foreign workers regarding their occupational safety in the construction industry in Malaysia. It was found that the existing laws in Malaysia relating to the issue are still lacking in enforcement and also lacking in preventive measures for the reduction of occupational safety and illness.on the construction site. An example is the accident and fatality of foreign workers in a construction site in Kuala Terengganu on 29 March 2010. Menteri Besar of Terengganu said that from the report, the accident was caused due to negligent and safety measures were not appropriate at the site. This research is conducted to examine why the existing laws in Malaysia is inadequate to protect the safety of foreign workers in the construction industry. Most of the information gained is from library based research including online database. Semi-structural interviews have also been carried out in order to obtain information on the issue. To conclude, this research identifies the problems of the occupational safety of foreign workers in the construction industry and gave suggestions to improve the enforcement of existing laws in Malaysia by providing some recommendations.